"Trusted to the ends of the earth?" An analysis of solicitors' disciplinary processes in England and Wales from 1994 to 2015. Issue 2 (4th May 2021) - Boon, Andrew; Whyte, Avis
ABSTRACT: This study deals with misconduct cases involving solicitors, the largest legal profession in England and Wales. It covers a 20 year period and focuses in detail on three points during that period: 1994–1996, 2008 and 2015. These points cover different stages during the evolution of the regulatory system from what was arguably the height of legal professionalism to the post-professional system initiated by the revolutionary Legal Services Act 2007. Drawing on detailed studies of disciplinary cases we examine the relationship between professional demography and modes of regulation in determining the outcomes of regulation.